(untitled) (Journal of Kidney Cancer, 2020)
Spontaneous retroperitoneal hemorrhage (SRH) is a rare emergency. It is usually encountered in patients on hemodialysis and is associated with high rate of morbidity and mortality. This is a case from the emergency department. The patient had unstable vitals with SRH following dialysis. Immediate exploration and nephrectomy using transverse lateral lumbotomy incision were done. Patients on hemodialysis are at a risk of SRH and frequent surveillance is recommended. Acquired cystic kidney disease (ACKD) can develop in hemodialysis patients and put them at risk for bleeding. Transverse lateral lumbotomy may be a safe option for direct access to the kidney in emergency kidney surgery